Acoustic Telemetry: A Tool to Monitor Fish Swimming Behavior in Sea-Cage Aquaculture - Muñoz, Lidia; Aspillaga, Eneko; Palmer, Miquel; Saraiva, João L.; Arechavala-Lopez, Pablo (Frontiers in Marine Science, 2020)
Acoustic telemetry techniques are very useful tools to monitor in detail the swimming behaviour and spatial use of fish in artificial rearing environments at individual and group levels. We evaluated the feasibility of using passive acoustic telemetry to monitor fish welfare in sea-cage aquaculture at an industrial scale, characterizing for the first time the diel swimming and distribution patterns of gilthead seabream (Sparus aurata) at fine-scale. Ten fish were implanted with acoustic tags equipped with pressure and acceleration sensors, and monitored in a commercial-size sea-cage for a period of one month. Overall, fish exhibited clear differences in day vs night patterns both on swimming activity and vertical distribution throughout the experiment. Space use increased at night after the implementation of structural environmental enrichment in the sea-cage. Acoustic telemetry may represent an advancement to monitor fish farming procedures and conditions, helping to promote fish welfare and product quality.